2010
DOI: 10.1007/s11899-010-0075-5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transplantation in Diffuse Large B-Cell Lymphoma: The Impact of Rituximab Plus Chemotherapy in First-line and Relapsed Settings

Abstract: Rituximab has improved the prognosis of patients with diffuse large B-cell lymphoma, but a high proportion of patients with advanced disease will relapse or will fail to achieve a remission with front-line treatment. Salvage chemotherapy, followed by high-dose chemotherapy or radiation therapy and autologous stem cell transplantation, remains the best treatment option for such patients, especially those who retain chemosensitivity. Allogeneic transplantation is under investigation in this setting, often as a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Therapeutic modalities for improving the treatment of DLBCL, such as the introduction of rituximab [21] and high-dose chemotherapy followed by autologous hematopoietic stem cell transplantation [22], may further improve the outcome of these patients. Well-designed randomized control studies with larger cohorts are urgently warranted to answer these questions.…”
Section: Resultsmentioning
confidence: 99%
“…Therapeutic modalities for improving the treatment of DLBCL, such as the introduction of rituximab [21] and high-dose chemotherapy followed by autologous hematopoietic stem cell transplantation [22], may further improve the outcome of these patients. Well-designed randomized control studies with larger cohorts are urgently warranted to answer these questions.…”
Section: Resultsmentioning
confidence: 99%
“…High‐dose chemotherapy followed by ASCT still remains an integral component of upfront treatment strategy in multiple myeloma patients allowing for improvement in response rate obtained by standard therapy or cytoreduction before allogeneic stem cell transplantation . Several studies have also demonstrated efficiency of ASCT as consolidation of first CR in mantle cell lymphoma or as salvage chemotherapy in relapsed diffuse large B‐cell lymphoma or follicular lymphoma .…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Moreover, several studies have shown that the addition of rituximab to salvage chemotherapy prior to auto-HCT has been associated with superior DFS and OS, as recently reviewed by Mounier and Gisselbrecht, 11 and Rodrigues et al 38 Of concern is the inferior response to rituximab-containing salvage regimens described in patients after prior rituximab treatment. 10 In the setting of allogeneic transplantation, the use of rituximab in conjunction with RIC regimens has been suggested.…”
Section: The Role Of Anti-cd20 Moabs Rituximabmentioning
confidence: 98%